Molecular theory of capillarity - Rowlinson, J. S. 1926- (Dover Publications, 2002)
History of thought on molecular origins of surface phenomena offers a critical and detailed examination and assessment of modern theories, focusing on statistical mechanics and application of results in mean-field approximation to model systems. Emphasis on liquid-gas surface, with a focus on liquid-liquid surfaces in the final chapters. 1989 edition.